Gim Multiplayer Beat ‘Em Ups Menggunakan Photon Unity Networking - Herman Thuan; Benedicto Raka (Universitas Ngeri Malang, 2021)
Beat Em' Ups is a type of game genre where players do battle in defeating all the enemies in large numbers either not using weapons or can use melee weapons. The game Beat Em'Ups was born at the beginning of its appearance in 1984 and as time went on it presented more and more interesting sub-genres in it with the classification of the Hack and Slash model, and the Spectacle Fighter model. The presence of a game engine like Unity with support for a multiplayer framework called Photon Networking makes it easier to develop Beat Em'Ups games that can be published on multiple platforms. The purpose of this research is to increase interactivity in Beat Em'Ups by implementing a player multiplayer system using Photon Unity Networking. This research produces a Windows game prototype with the game testing method carried out with a black box. Evaluation and user suggestions for the development of this game were carried out in the form of a survey of 23 online game players using an online form. Based on the results of data testing, 78.6 percent of users stated that they were satisfied with the Beat Em'Ups gameplay model presented in the resulting multiplayer mode, 82.61percent of users felt they had a very good experience with the multiplayer game Beart Em'Ups played, and 91, 3 percent rated very satisfied with the display of the multiplayer interface provided. Beat Em' Ups merupakan jenis genre gim dimana pemain melakukan pertempuran dalam mengalahkan seluruh musuh dalam jumlah besar baik tidak menggunakan senjata atau dapat menggunakan senjata jarak dekat. Gim Beat Em’Ups lahir diawal kemunculan tahun 1984 dan seiring berjalannya waktu semakin menghadirkan sub-genre yang menarik didalamnya dengan klaslifikasikan model Hack and Slash, dan model Spectacle Fighter. Hadirnya gim engine seperti Unity dengan dukungan framework multiplayer bernama Photon Networking maka semakin memudahkan dalam mengembangkan gim bergenre Beat Em’Ups yang dapat dipublikasikan ke beberapa platform. Tujuan penelitian ini adalah untuk meningkatkan interaktivitas pada gim Beat Em’Ups dengan menerapkan sistem multiplayer pemain menggunakan Photon Unity Networking. Penelitian ini menghasilkan prototype gim windows dengan metode pengujian gim yang dilakukan dengan black box. Evaluasi dan saran pengguna terhadap pengembangan gim ini dilakukan dalam bentuk survey kepada 23 orang pemain gim online dengan menggunakan form online. Berdasarkan hasil pengujian data, 78,6 persen pengguna menyatakan puas dengan model gameplay Beat Em’Ups yang disajikan dalam mode multiplayer yang dihasilkan, 82,61persen pengguna merasa memiliki pengalaman yang sangat baik terhadap multiplayer gim beart Em’Ups yang mainkan dan 91,3 persen menilai sangat puas dengan tampilan interface multiplayer yang diberikan.